Answer: im lonely 2 but the answer is shrek!
Step-by-step explanation:
The sum means addition.
Add the like terms together.
4x^3+2x^2-4x+3
+ 7x^3-4x^2+7x+8
4x^3 + 7x^3 = 11x^3
2x^2 + -4x^2 = -2x^2
-4x +7x = 3x
3 +8 = 11
The answer is : 11x^3 - 2x^2 + 3x + 11
If x is the first of the integers then the statement is:
(x) , (x+2) , (x+4) , (x+6)
This means that the smallest is x and the largest is x + 6
so:
3(x) + 2(x+6) = 293
3x + 2x + 12 = 293
5x = 281
x = 56.2
This gives us a none integer (decimal)
What now?
Wait remember how x started as the lowest? what if x was the highest instead?
x, x-2, x-4, x-6
so:
3(x-6) + 2(x) = 293
5x = 315
x = 62.2
This is as close as have gotten to the answer
Cant seem to get an integer.
Maybe error in the question or some bad math on my part.
Answer:
the first ones >
Step-by-step explanation:
the second ones <
Answer:
n=18
Step-by-step explanation:
7n+11?
n=7+11
7+11=18
n=18